Epidemiological and sociodemographic profile of women in Domestic and Family Violence situation in a municipality in south Bahia (Research, Society and Development, 2023)
Objective: to describe the epidemiological, sociodemographic characteristics and forms of occurrences of Domestic and Family Violence against Women registered at the Police Station Specialized in Assistance to Women (DEAM) in the municipality of Itabuna, Bahia. Methodology: This is an epidemiological, descriptive study, which used DEAM records of occurrences, in the municipality of Itabuna, Bahia, Brazil, from 2013 to 2020. Results: During the period from 2013 to 2020, 8816 occurrences of VDFCM were recorded, and in 2017 there was a higher proportion (16.3%) of records. It was found that most women were brown (84.3%), aged between 35-64 years (40.7%), heterosexual (99.3%), and residents of Module 4 (34.5%). In addition, the motivation for intrafamily fights prevailed (73.7%); the means used others (63.9%); and psychological violence (37.1%). Conclusions: The Domestic and Family Violence against Women in the municipality of Itabuna showed a tendency to reduce occurrence records from 2017 to 2020. It is suggested to carry out new longitudinal analytical epidemiological studies, as well as studies with qualitative approaches, which investigate women in situations of violence, the perpetrators of violence, and/or services aimed at Domestic and Family Violence against Women care.